An engineer's guide to automated testing of high-speed interfaces - Moreira, Jose; Werkmann, Hubert (Artech House, 2010)
Offers an introduction to the high-speed digital testing with automated test equipment (ATE). This title covers the critical aspects of the subject, from high-speed digital basics, ATE instrumentation for digital applications, and test and measurements, to production testing, support instrumentation and text fixture design.